TIOtropium Safety and Performance In Respimat® (TIOSPIRTM): Analysis of Asian cohort of COPD patients. Issue 8 (4th August 2016) - Zhong, Nanshan; Moon, Hwa S.; Lee, Kwan H.; Mahayiddin, Aziah A.; Boonsawat, Watchara; Isidro, Marie G.D.; Bai, ChunXue; Mueller, Achim; Metzdorf, Norbert; Anzueto, Antonio
ABSTRACT: Background and objective: The TIOtropium Safety and Performance In Respimat (TIOSPIR) trial showed similar safety and exacerbation efficacy profiles for tiotropium Respimat and HandiHaler in patients with COPD. The TIOSPIR results for patients in Asia are presented here. Methods: TIOSPIR evaluated once‐daily tiotropium Respimat 5 and 2.5 µg with HandiHaler 18 µg in patients with COPD. Primary endpoints included time to death and time to first COPD exacerbation. Safety and exacerbation efficacy profiles were determined for the Asian region, and for Asia (all treatment arms pooled) versus the rest of the world (RoW). Results: In Asia ( n  = 2356), time to death was similar for Respimat 5 and 2.5 µg versus HandiHaler 18 µg (hazard ratio (HR) (95% CI): 0.96 (0.67, 1.38) and 1.23 (0.87, 1.73)). Risk of COPD exacerbation was similar for Respimat 5 µg, but increased for 2.5 µg versus HandiHaler 18 µg (HR (95% CI): 0.99 (0.85, 1.15) and 1.17 (1.00, 1.35)). Time to death in Asia and RoW was similar (HR (95% CI): 1.15 (0.99, 1.35)). Time to first COPD exacerbation was longer (HR (95% CI): 0.84 (0.78, 0.89)) and exacerbation rates were lower in Asia, but severe exacerbations were more frequent than in the RoW. Risk of major adverse cardiovascular events was similar for both regions. Conclusion: Similar safety and exacerbation efficacy profiles were observed for tiotropium Respimat 5 µg and HandiHaler 18 µg in patients with COPD from Asia, analogous to the global analysis. Asian patients had lower risk of, and fewer exacerbations overall, but a higher proportion of severe exacerbations than in the RoW. Abstract : Asian cohort analysis in TIOtropium Safety and Performance In Respimat In Respimat ® (TIOSPIR TM ) COPD trial demonstrates that, analogous to the global analysis, tiotropium Respimat 5 µg and HandiHaler 18 µg have similar safety and exacerbation efficacy. However, patients in Asia had fewer, but more severe, exacerbations than patients from the rest of the world. See Editorial, page 1340 Watch the video abstract